2012
DOI: 10.1177/1753193412469127
|View full text |Cite
|
Sign up to set email alerts
|

Trapeziometacarpal narrow pseudarthrosis: a new surgical technique to treat thumb carpometacarpal joint arthritis

Abstract: We describe a technique that arose from the observation of the clinical outcome of failed arthrodeses of the thumb carpometacarpal joint. In these cases a pseudoarthrosis developed which, surprisingly, rarely lead to a poor clinical outcome. Thus we developed a simple technique which deliberately caused the formation of a narrow pseudoarthrosis in the carpometacarpal joint. We present a retrospective review of 248 consecutive patients treated for Eaton stages II and III osteoarthritis. We observed a statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
(36 reference statements)
1
19
1
Order By: Relevance
“…The most important conclusion from our series, is that the subjective and objective variables did not correlate with bone union across the thumb CMC joint. In addition the patients with a 'narrow pseudoarthrosis' had a lower incidence of STT joint arthritis, confirming the hypothesis of Rubino et al (2013) who did not find any deterioration of the STT joint in their series. Damen et al (2001) noted that, in their patients treated with thumb CMC joint arthrodesis, the radiographic progression and severity of STT arthritis were greater in the fused thumb than in the contralateral thumb.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The most important conclusion from our series, is that the subjective and objective variables did not correlate with bone union across the thumb CMC joint. In addition the patients with a 'narrow pseudoarthrosis' had a lower incidence of STT joint arthritis, confirming the hypothesis of Rubino et al (2013) who did not find any deterioration of the STT joint in their series. Damen et al (2001) noted that, in their patients treated with thumb CMC joint arthrodesis, the radiographic progression and severity of STT arthritis were greater in the fused thumb than in the contralateral thumb.…”
Section: Discussionsupporting
confidence: 81%
“…A recent study has developed a new surgical technique that aims to create a narrow CMC pseudoarthrosis to transform the joint from a synovial diarthrodial joint into a fibrous joint (Rubino et al, 2013). Good results are reported suggesting that a fibrous non-union may provide a satisfactory result.…”
Section: Introductionmentioning
confidence: 98%
“…10) By observing the good clinical outcome of a failed arthrodesis of the thumb carpometacarpal joint, recently some authors have shown good results by deliberately creating a narrow pseudoarthrosis in the TM joint, although this is not recommended for stage IV. 11) TM joint arthroplasty is another option which aims at preserving the length of the thumb with soft tissue balancing but this technique is weighted down by its high rate of complications, such as radiographic subsidence into the trapezium, bone loosening, migration and dislocation, especially when using Moje Acamo CMC 1 implants and Elektra and Pyrocarbon implants. [12][13][14][15] Good results were presented by Goubau et al 16) after joint replacement with ivory prosthesis (Memometal, Stryker Corporate) in 22 patients included in a 5-year prospective follow-up study.…”
Section: Discussionmentioning
confidence: 99%
“…3 Rubino et al reported that patients with nonunion after arthrodesis only complain of pain until the metalwork has been removed. 4 This suggests that the retained hardware may be the source of pain. Patients with nonunion can have persistent pain and weakness with activities even when hardware is not present, however.…”
Section: Adverse Effectsmentioning
confidence: 98%
“…4 Of these 5 patients, one patient (20%) had a nonunion and underwent revision arthrodesis with plates and iliac crest bone graft. This failed to unite, and was again revised with tensionband wiring and bone grafting resulting in union.…”
Section: Literature Reviewmentioning
confidence: 99%